2018
DOI: 10.1039/c8ra00555a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(3-hexylthiophene): improvement of regioregularity and energy band gap

Abstract: The regioregularity and band gap of P3HT, an organic solar cell donor polymer, were improved. Oxidative coupling enhanced regioregularity, voltammetric p-doping broadened the optical absorption band and a molar mass increase reduced the band gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 39 publications
(37 reference statements)
7
35
0
Order By: Relevance
“…Peak at 1107.06 cm -1 show the presence of C-H aromatic ring. The stretching vibration of the thiophene ring were detected at 860.16 cm -1 these results are agree with [4][5][6].…”
Section: Results and Discussion 1-fourier Transform Infrared Radiatiosupporting
confidence: 83%
“…Peak at 1107.06 cm -1 show the presence of C-H aromatic ring. The stretching vibration of the thiophene ring were detected at 860.16 cm -1 these results are agree with [4][5][6].…”
Section: Results and Discussion 1-fourier Transform Infrared Radiatiosupporting
confidence: 83%
“…Moreover, the regioregular sample also shows a higher value of V OC , according to its lower HOMO level energy. The obtained results are in good agreement with the findings reported by Malik et al in a recent work, [38] in which the importance of structural regioregularity in the donor polymer is evidenced. The authors observed that highly regioregular ED-polymers show an enhanced mobility of excitons and a compressed bandgap, which can improve the absorption efficiency of the solar spectrum.…”
Section: Photovoltaic Propertiessupporting
confidence: 93%
“…Figure 1 a shows the main IR bands of P3HT, which are peaked at 723, 810, 1032, 1165, 1462, 1510, 1735, 2854, 2924 and 3113 cm −1 , they being assigned to the following vibrational modes: rocking CH 2 , out of plane bending C-S in thiophene ring α, α’ disubstituted, aromatic C-H stretching, thiophene ring, asymmetrical C=C in thiophene ring, C=O stretching, symmetric C-H stretching in CH 2 moieties, C-H in hexyl group and sp 2 C-H stretching in aromatic compounds, respectively [ 8 , 21 ]. The IR bands at 617 and 1381 cm −1 were attributed to the vibrational modes of the distorted parts of polymer and the deformation of -CH 3 group belonging to the defects present in the P3HT macromolecular chains, respectively [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%